Implementasi Model Cooperative Learning Teknik Stad Untuk Meningkatkan Kemampuan Berpikir Kreatif Mengajar dalam Program Latihan Profesi - Heti Suherti; Tetty Fatimah Tsuroya (Jurnal Soshum Insentif, 2019)
Real-life viewing as a practice for prospective teachers is not automatically and instantly formet, but supported by various factors including field conditions (classes and students), mastery of materials, methods, models, technigues, tactics and supported by media, tools, relevant sources and can give alternative constructive-supportive solutions, mental preparedness. Skills and abilities of performance to support professional training program. The puporse of the research is to find the difference of creative thinking ability to teach profession training program that uses and does not use cooperative learning model of STAD technique on the curriculum study subject of teaching planning (micro practice). The method used in this research is guasi experiment method with descriptive survey, fiel study, instrumental, and literature study. The population of 5 classed with 151 people, systematic sampling technique taken random, distance from 2 experimental class with 32 people, and 2 control classes with 31 people. The data analysis technique used is t tes with the real level α = 0,05 using SPSS version 16,0 for windowns. The results of this study indicate thet there is a difference in the ability of creative thinking teaching on the class that uses and does not use the cooperative learning model of STAD technique on the curriculum study subject of teaching planning (micro practice), so the increase in the profession training program at school is 30,7%.